Analisis Kehandalan dan Ketanggapan Dalam Rangka Memberi Pelayanan di Kantor Desa Sumberwulan - Alfani, Karisma; Kuswantoro, Agung (Universitas Negeri Semarang, 2024)
This research aims to determine the reliability and responsiveness of Sumberwulan village officials in providing administrative services to the Sumberwulan village community. This type of research is qualitative descriptive analysis, data collection techniques in this research are observation, interviews and documentation methods. The results of this research show two very prominent dimensions of service quality, namely the reliability dimension and the responsiveness dimension. Sumberwulan village officials have been able to implement the dimensions of reliability well and in accordance with the SOP. Sumberwulan village officials have been able to implement dimensions of responsiveness. All indicators have been fully implemented in the service process. This research provides information as a form of evaluation for the Sumberwulan Village Office in providing administrative services to the community.